Efficacy of immunotherapy in KRAS-mutant advanced NSCLC: A real-world study in a Chinese population - Peng, Lixiu; Guo, Jun; Kong, Li; Huang, Yong; Tang, Ning; Zhang, Juguang; Wang, Minglei; He, Xiaohan; Li, Zhenzhen; Peng, Yonggang; Wang, Zhehai; Han, Xiao (Frontiers in Oncology, 2023)
Background Immunotherapy has improved the clinical outcomes of patients with advanced non-small cell lung cancer (NSCLC). However, in patients with Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations, the superior efficacy of immunotherapy has not been elucidated and especially in real-world practice. Our study aimed to use real-world data to assess the efficacy of immunotherapy in KRAS-mutant NSCLC in a Chinese cohort. Methods In this retrospective cohort study, we extracted the clinical, molecular, and pathologic data from the electronic health records of patients with advanced KRAS-mutant NSCLC at Shandong Cancer Hospital between January 2018 and May 2022. Furthermore, we evaluated the progression-free survival (PFS) and overall survival (OS) of the included patients. Results Between January 2018 and November 2020, 793 patients were identified with stage IIIB-IV NSCLC and a total of 122 patients with KRAS mutations were included in the analysis. The majority of patients were diagnosed with stage IV (82.0%) adenocarcinoma (93.4%), along with a history of smoking (57.4%). Of these, 42% of patients received anti-PD-(L)1 with or without chemotherapy (Immunotherapy-based regimens), while 58.2% of patients received chemotherapy (Chemotherapy-based regimens). The median overall survival (mOS) in this cohort was 22.9 months (95% CI: 14.1–31.7), while the median-progression-free survival (mPFS) was 9.4 months (95% CI: 6.6–12.1). Patients receiving immunotherapy-based regimens displayed better mOS than those receiving chemotherapy-based regimens (45.2 vs. 11.3 months; P=1.81E-05), with no statistical difference observed in the mPFS (10.5 vs. 8.2 months; P=0.706). Patients receiving immunotherapy-based regimens either in the first line (P=0.00038, P=0.010, respectively) or second-line setting (P=0.010, P=0.026, respectively) showed benefits in both PFS and OS. Subgroup analysis indicated that in patients having KRAS G12C or non-KRAS G12C mutant types, immunotherapy showed benefits of better OS (P=0.0037, P=0.020, respectively) than chemotherapy. Moreover, in advanced NSCLCs patients with or without KRAS/TP53 co-mutation the immunotherapy-based regimen achieved longer OS and PFS than chemotherapy-based regimens. Conclusions In the Chinese population of patients with KRAS-mutant advanced NSCLC, immunotherapy-based regimens achieved longer OS than chemotherapy-based regimens, which was independent of first or second-line setting, as well as KRAS mutational subtypes.